Acute pulmonary edema returning to a High Altitude Environment: report of a case observed in Huaraz, Ancash, Peru - Lopez de Guimaraes, Douglas (2018)
Introduction: Sudden exposure to a high altitude environment in a susceptible individual may lead to the occurrence of high altitude acute pulmonary edema, a condition that has two types: ascending and returning; the latter affects people native from high altitude when they return to their places, after spending some time in low altitude environments.Case Report: We present the case of a healthy 17-year old male patient born in a high altitude environment (3400 meters above sea level) who was admitted in Victor Ramos-Guardia Hospital in Huaraz (3100 meters above sea level), 48 hours after returning back to his home place, subsequent to having been in Lima for 21 days. He was brought to the emergency room with productive cough, dyspnea at rest, chest pain, tachypnea, tachycardia, and abnormal respiratory sounds (crackles). Chest X-ray films and hypoxemia contributed to make a precise diagnosis. In spite of his severely deteriorated condition, he improved after 48 hours and was discharged one day later. Pathophysiology mechanisms, therapy, and prevention of high altitude pulmonary edema are reviewed.